2022
DOI: 10.3389/fvets.2022.866106
|View full text |Cite
|
Sign up to set email alerts
|

“When a dog bites someone”: Community and service provider dynamics influencing access to integrated bite case management in Chad

Abstract: This study aims to identify factors on the community, the human health and the animal health provider level that determine access to Post Exposure Prophylaxis (PEP) and animal rabies diagnosis in the light of a future integrated bite case management (IBCM) approach for rabies control in Chad. The study was embedded in an overall project conducted from 2016 to 2018, to determine rabies burden and vaccine demand in West and Central Africa. Data collection took place during the projects closing workshops with sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We found that an increase of USD 100.00 in a neighborhood's median income was associated with a 4.9% (95% CI: 3.8-6.1; p < 0.001) lower incidence rate of dog bites. Such findings may indicate that low income and local development may also mirror local animal health with a lack of or insufficient basic veterinary services, including rabies vaccination, dog neutering/spaying, and responsible guardianship [11,28], particularly in vulnerable communities. A survey conducted by our research group in Curitiba showed an inverse correlation between neighborhood income and dog biting amongst local postmen [10], reflecting that households with a better infrastructure reduced the overall occupational exposure to dog bites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that an increase of USD 100.00 in a neighborhood's median income was associated with a 4.9% (95% CI: 3.8-6.1; p < 0.001) lower incidence rate of dog bites. Such findings may indicate that low income and local development may also mirror local animal health with a lack of or insufficient basic veterinary services, including rabies vaccination, dog neutering/spaying, and responsible guardianship [11,28], particularly in vulnerable communities. A survey conducted by our research group in Curitiba showed an inverse correlation between neighborhood income and dog biting amongst local postmen [10], reflecting that households with a better infrastructure reduced the overall occupational exposure to dog bites.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, specific demographic groups, such as children, may be more likely to seek or be taken to medical care [2,22]. Another potential bias source may be associated with access to health services; certain populations within a city may receive different disinformation about access and show refusal of health resources [28], which may also lead to biased demographic or geographical reporting of dog bites [33,34]. As a consequence of the above factors, the number and incidence of dog biting herein may be even higher; previous studies indicated a three-fold underestimation between official reports and actual cases [22].…”
Section: Discussionmentioning
confidence: 99%
“…This requires closer cooperation between public health and veterinary services. Experience has shown that implementing an IBCM within a One Health framework can significantly improve rabies surveillance and performance and access to post-exposure prophylaxis (PEP) in a region [87][88][89][90][91][92].…”
Section: Discussionmentioning
confidence: 99%
“…This requires closer cooperation between public health and veterinary services. Experience has shown that implementing an IBCM within a One Health framework can significantly improve rabies surveillance and performance and access to PEP in a region [88][89][90][91][92][93].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%